Dynamic Corneal Response for Different Air-Puff Stimuli in Ex Vivo Animal Model Measured with SS-OCT System with Two Sample Arms - Ewa Maczynska-Walkowiak; Daniel Ruminski; Grzegorz Gondek; Bartlomiej J. Kaluzny; Karol Karnowski; Ireneusz Grulkowski (Applied Sciences)
This study demonstrates the use of a dual-sample arm swept-source optical coherence tomography (SS-OCT) instrument coupled with air-puff stimulation to assess corneal displacement in an ex vivo porcine eye model. The air-puff SS-OCT system enables correction of corneal deformation for eye globe retraction, providing a comprehensive quantitative analysis of corneal apex deformation dynamics under varying intraocular pressure (IOP) levels and air-puff stimulus strengths. Spatio-temporal characterization of those stimuli was performed. The results showed that the cornea stiffened with increased IOP, and reducing the stimulus amplitude decreased the correlation between parameters describing corneal dynamics and IOP. However, maximum displacement and corneal response time exhibited very strong correlations regardless of the strength of the applied air-puff. These findings suggest that softening air-puff stimulation may impact the accuracy of non-contact tonometers in measuring IOP and corneal biomechanical properties.